Separation Axioms via Ç Â SemiÂ gÂ Open Sets - M. A. Abdel Karim; A. I. Nasir (Ibn Al-Haitham Journal for Pure and Applied Sciences, 2020)
The notions ÇÂsemiÂgÂclosedness and ÇÂsemiÂgÂopenness were used to generalize and introduced new classes of separation axioms in ideal spaces. Many relations among several sorts of these classes are summarized, also.